2019
DOI: 10.3389/fmicb.2019.01890
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Activities of Nemonoxacin and Other Antimicrobial Agents Against Human Mycoplasma and Ureaplasmas Isolates and Their Defined Resistance Mechanisms

Abstract: Nemonoxacin, a newly developed non-fluorinated quinolone (NFQ), selectively inhibits bacterial DNA topoisomerase activity. However, its activities against Mycoplasmas have rarely been studied to date. Herein, the activities of nemonoxacin were evaluated against clinical isolates of 50 Mycoplasma pneumoniae , 20 Mycoplasma hominis , and 77 Ureaplasma spp., and they were compared to fluoroquinolones, tetracyclines, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Valentine-King and Brown found U. parvum to have low resistance to azithromycin (MIC of �0.5-2 μg/ml) for 60 isolates from the United States and only slightly higher MICs for U. urealyticum (MIC of �0.5-4 μg/ml) [45]. A similar trend towards higher MIC for U. urealyticum was reported from China [46], and a study analyzing ureaplasmas from neonates from the UK found no resistance to macrolides and no different activity of azithromycin, but a significantly higher erythromycin MIC for U. urealyticum [47]. However, these in vitro studies may not reflect the in vivo activity, where factors like biofilm or pH may influence the activity of antibiotics.…”
Section: Plos Onesupporting
confidence: 60%
See 1 more Smart Citation
“…Valentine-King and Brown found U. parvum to have low resistance to azithromycin (MIC of �0.5-2 μg/ml) for 60 isolates from the United States and only slightly higher MICs for U. urealyticum (MIC of �0.5-4 μg/ml) [45]. A similar trend towards higher MIC for U. urealyticum was reported from China [46], and a study analyzing ureaplasmas from neonates from the UK found no resistance to macrolides and no different activity of azithromycin, but a significantly higher erythromycin MIC for U. urealyticum [47]. However, these in vitro studies may not reflect the in vivo activity, where factors like biofilm or pH may influence the activity of antibiotics.…”
Section: Plos Onesupporting
confidence: 60%
“…A similar trend towards higher MIC for U . urealyticum was reported from China [ 46 ], and a study analyzing ureaplasmas from neonates from the UK found no resistance to macrolides and no different activity of azithromycin, but a significantly higher erythromycin MIC for U . urealyticum [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of quinolone resistance involves mutations in the gyrA and gyrB subunits of DNA gyrase and parC and parE subunits of topoisomerase IV that probably arise because of antimicrobial selective pressure [ 17 , 21 ]. Wang et al reported that nemonoxacin, a novel nonfluorinated quinolone, may have increased antibacterial activity and decreased adverse effects on account of its C-8-methoxy structure on the quinolone ring [ 22 ]. The resistance rates for tetracyclines including tetracycline, doxycycline, and minocycline remained below 3%, and the resistance rates for macrolides including josamycin, roxithromycin, clarithromycin, and azithromycin were approximately 20%.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance mechanisms of MRMP have been demonstrated by in vitro selection that involves point mutations in the peptidyl transferase loop of 23S rRNA and point mutations, insertions, or deletions in ribosomal proteins L4 and L22 ( Lucier et al., 1995 ; Pereyre et al., 2004 ; Ou et al., 2015 ; Waites et al., 2017 ). Some of these changes were observed in clinical MRMP isolates ( Morozumi et al., 2005 ; Xin et al., 2009 ; Wang et al., 2019 ), while some were not ( Pereyre et al., 2004 ; Ou et al., 2015 ), probably because these MRMP strains were induced by subminimum inhibitory concentrations of macrolide antibiotics. The investigation of macrolide resistance mechanisms in M. pneumoniae has mainly been focused on the single 23S RNA gene and ribosomal protein genes, and so further analysis on other potential resistance mechanisms is required.…”
Section: Introductionmentioning
confidence: 99%